Mediated Role of New Environmental Paradigm (NEP) Between Environmental Concerns and Students’ Green Purchase Behavior (GPB) Interfered by Big-5 Personality - Yuniasih, Idah; Putrawan, I Made; ., Nadiroh (International Journal of Membrane Science and Technology, 2023)
Human basic needs should be filled with satisfaction in daily life for survival and growth. One of the behavior, in this case, is the ability of the people to consume goods they need, that is why they are called consumers. To satisfy their needs, they have to use their purchase behavior for the transaction, which is called green transaction when they perceive that behavior would be meant to preserve our nature since most of the goods as products derived from the exploitation of nature. That was why this research was urgently conducted to find out the information, on what factors should be considered that affect people’s green purchasing behavior (GPB). For this purpose, a causal survey was used by selecting randomly 160 university students as a sample. There were four instruments developed to measure green purchase behavior (reliability was 0.947), environmental concern (rel. was 0.927), students’ new environmental paradigm (NEP/rel. was 0.961), and big-5 personality (rel. was 0.972). Data were analyzed by path analysis. The research results revealed that all those exogen variables found affected directly and significantly students’ GPB. It was found also the good role of students’ NEP which was proven to be highly significant as mediated variable between environmental concerns with students’ GPB even though it was interfered with by students’ personalities empirically. Therefore, it could be concluded that in developing university campus policies, it is well suggested to involve those factors such as students’ environmental concerns, their NEP, and personalities as well to be taken into consideration.